Expansion of logistics infrastructure in the oil sector as a form of improving Poland's energy security - Piękoś, Dominik; Suduł, Przemysław; Augustyn, Sławomir (Scientific Journal of Bielsko-Biala School of Finance and Law, 2023)
Energy security refers to a country’s ability to provide stable access to energy, including energy resources such as oil. In Poland, PKN Orlen and PERN S.A. are the key companies managing oil logistics and processing for public and private use. A special purchaser of petroleum substances is the Armed Forces of the Republic of Poland, which are a fundamental element of the State Defense System, which use the acquired fuels to ensure the effective implementation of state defense and security policies. The article presents the possibilities of improving the logistics infrastructure in the oil sector through critical modeling of the elements that make up the logistics supply chain (project 116B 844/2023) with the use of innovative technologies. The ongoing investments enable the increase of storage space and faster transport of petroleum products using new technologies, which translates into increased energy security of the country.